2021
DOI: 10.18488/journal.65.2021.81.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Drying Characteristics and Kinetics of Okra at Different Thickness

Abstract: The effect of sample thickness and temperature on the drying characteristics of okra was investigated using a laboratory moisture analyser (Denver instrument IR-30) at sample thickness of 5mm, 10mm and 15mm and temperatures of 90 o C, 100 o C and 110 o C respectively. The experimental data was fitted into three thin layer mathematical models. The fitness of the experimental data were evaluated using statistical analysis. It was observed that data fitted well with the Page model for the temperatures and sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Besides, at a constant drying temperature, D eff values increase with thickness. Torubeli et al (2021) studies of the drying kinetics of okra at various thicknesses have shown that values at all temperatures of 5mm are higher than values at 10mm and 15mm. This is because diffusion channels are smaller in larger samples and moisture is more readily migrated, resulting in greater D eff (Deng et al, 2018).…”
Section: Effective Diffusion Coefficient Calculationmentioning
confidence: 88%
“…Besides, at a constant drying temperature, D eff values increase with thickness. Torubeli et al (2021) studies of the drying kinetics of okra at various thicknesses have shown that values at all temperatures of 5mm are higher than values at 10mm and 15mm. This is because diffusion channels are smaller in larger samples and moisture is more readily migrated, resulting in greater D eff (Deng et al, 2018).…”
Section: Effective Diffusion Coefficient Calculationmentioning
confidence: 88%